Simplify the complex fraction:

[(√x-√y)/(√x+√y)-(√x+√y)/(√x-√y)] / [(√x-√y)/(√x+√y)+(√x+√y)/(√x-√y)]

Show complete solution.

Expert Answers

An illustration of the letter 'A' in a speech bubbles

You must find out the common denominator of fractions from numerator. This common denominator is (√x+√y)(√x-√y). This special product is the difference of squares x-y.

You must multiply the fractions from numerator by the common denominator.

[(√x-√y)^2 - (√x+√y)^2]/(x-y)

You will expand the squares with formula:

(a+b)^2=a^2+2ab+b^2

(a-b)^2=a^2-2ab+b^2

(√x-√y)^2=x-2√xy+y

 (√x+√y)^2=x+2√xy+y

(√x-√y)^2 - (√x+√y)^2=x-2√xy+y-x-2√xy-y=-4√xy

You will repeat the steps to calculate the addition from denominator.

[(√x-√y)^2 + (√x+√y)^2]=x-2√xy+y+x+2√xy+y=2x+2y=2(x+y)

You will write the resulting fraction:

[-4√xy/(x-y)]/[2(x+y)/(x-y)]

Multiply the fraction from numerator by the reversed fraction from denominator.

[-4√xy/(x-y)]*[(x-y)/2(x+y)]

Simplify by x-y => [-4√xy/2(x+y)] = -2√xy/(x+y)

Answer: The result of fraction simplification is -2√xy/(x+y).

See eNotes Ad-Free

Start your 48-hour free trial to get access to more than 30,000 additional guides and more than 350,000 Homework Help questions answered by our experts.

Get 48 Hours Free Access
Approved by eNotes Editorial